2003
DOI: 10.1128/aem.69.1.641-643.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Redox Dye 5-Cyano-2,3-Tolyl-Tetrazolium Chloride for Activity Studies by Simultaneous Use of Microautoradiography and Fluorescence In Situ Hybridization

Abstract: Three microscopic in situ techniques were used simultaneously to investigate viability and activity on a single-cell level in activated sludge. The redox dye 5-cyano-2,3-tolyl-tetrazolium chloride (CTC) was compared with microautoradiography (MAR) and fluorescence in situ hybridization (FISH) to indicate activity of cells in Thiothrix filaments and in single floc-forming bacteria. The signals from MAR and FISH correlated well, whereas only 65% of the active Thiothrix cells and 41% of all single cells were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…1) indicates that not all cells are killed instantly, but rather many continue to function hours after exposure to CTC. In a study combining microautoradiography, fluorescent in situ hybridization and CTC, Nielsen et al (2003) found that all cells labeled with CTC were also labeled as positive by the other 2 techniques, thus discrediting the idea that CTC toxicity would impair the ability of scoring these cells as positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) indicates that not all cells are killed instantly, but rather many continue to function hours after exposure to CTC. In a study combining microautoradiography, fluorescent in situ hybridization and CTC, Nielsen et al (2003) found that all cells labeled with CTC were also labeled as positive by the other 2 techniques, thus discrediting the idea that CTC toxicity would impair the ability of scoring these cells as positive.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that these procedures caused unbalanced bacterial growth and high respiration rates in small bacteria, resulting in a CTF granule that broke the cell. Large bacteria, such as the benthic bacteria that Epstein & Rossell (1995) used for their experiments, or most coastal and freshwater bacteria may well be large enough to accommodate a large CTF granule (or even >1 crystal cell -1 if they are sufficiently large; Nielsen et al 2003) without cell breakage. It is important to mention here that the relationship between 'missing cells' and red-only particles reported in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Various fluorescent probes have the ability to explore different properties of the cell, such as enzyme activity (Kaneshiro et al, 1993;Diaper & Edwards, 1994a, 1994bEndo et al, 1997;Bunthof et al, 1999;Bunthof et al, 2001;Ben-Amor et al, 2002;Luppens et al, 2003); cytoplasmic membrane permeability (Magariños et al, 1997;Porter et al, 1997;Williams et al, 1998;Gregori et al, 2001;Hewitt & Nebe-Von-Caron, 2001), membrane potential (Mason et al, 1995;Langsrud & Sundheim, 1996;Lopes-Amoros et al, 1997;Ludovico et al, 2001), respiratory activity (Kaprelyants & Kell, 1993a, 1993bGunasekera et al, 2003;Yamaguchi et al, 2003;Nielsen et al, 2003), relative DNA content (Sgorbati et al, 1996;Bernander et al, 1998) and pH gradient (Breeuwer et al, 1996;Chitarra et al, 2000). Several of these parameters can be used as indicators of viability.…”
Section: Introductionmentioning
confidence: 99%
“…The CTC reduction method has been used to detect viable or respiring cells of microorganisms in purified and drinking water 10,23,31,32) , groundwater 17) , aquatic ecosystems 9,14,26,28,[34][35][36][37][38] , sediment 16,28) , soil 7,33,45,46) and bioreactors 11) . This method also has been applied to wastewater and activated sludge systems 27,44) . In addition, it has been shown that the viability of anaerobic bacteria is detectable by CTC staining 6,15) .…”
mentioning
confidence: 99%
“…Recently, the CTC staining method was also compared to microautoradiography and fluorescence in situ hybridization (FISH) to detect viable bacteria in activated sludge 27) . In most cases, the CTC staining method was shown to give unstable scores as being positive or to have low staining efficiency compared to other viability tests.…”
mentioning
confidence: 99%